“Plan de comunicación de la agenda de competitividad del GADPCH y su incidencia en la ciudadanía de riobamba, durante el período febrero- agosto 2012” - Guzmán Paguay, Diego Armando (2016)
The Competitiveness Agenda Chimborazo is a provincial project that aims to raise the competitive level of all industries that provide alternative land socioeconomic development in the province of Chimborazo. To view this joint was performed and implemented the Communication Plan Competitiveness Agenda Chimborazo which is a comprehensive planning tool that establishes a direct link between citizens of Riobamba and the Competitiveness Agenda, using mass media and alternative Extension and validation of plans, programs and actions that were made in the productive sectors of the territory. This research is based on the diagnosis, analysis and management of communication processes that were deployed in the Communication Plan of the Competitiveness Agenda decentralized autonomous government of the province of Chimborazo (GADPCH) and the impact it had on the citizens of Riobamba. In the Communication Plan of the Competitiveness Agenda identified the media that were used and which went public, also found significant differences in terms of publication, periodicity and information processing. At the same time in order to support the information gathered, presents arguments and criteria related sources topic officials and authorities of different public and private institutions that form the Committee of Management Competitiveness Agenda. Thus, following an investigation that was done for the Communication Plan of GADPCH Competitiveness Agenda, it was identified that the activities and communication strategies that were performed on a limited impact on the citizens of Riobamba, during the period February to August 2012.